2011
DOI: 10.1186/1471-2318-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate medication use among the elderly: a systematic review of administrative databases

Abstract: BackgroundInappropriate medication use (IMU) by elderly people is a public health problem associated with adverse effects on health. There are a number of methods for identifying IMU, some involving clinical judgment and others, consensually generated lists of drugs to be avoided. This review aims to describe studies that used information from insurance company and social security administrative databases to assess IMU among community-dwelling elderly and to present the risk factors most often associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
150
7
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(199 citation statements)
references
References 48 publications
(67 reference statements)
27
150
7
15
Order By: Relevance
“…15,16 In our study, we found the average number of drugs prescribed was 5.56 per prescription. Similar studies carried out among geriatric patients in another place of Nepal, 17 Turkey, 18 USA, 13 India, 6 Brazil, 19 The less number of drugs prescribed in our study compared to studies conducted in other countries might be due to a functional health insurance policy for the elderly in those countries which might have provided easier access to medications. The most common form of morbidities found in this study was from cardiovascular system (47.0%) with hypertension.…”
Section: Discussionsupporting
confidence: 49%
“…15,16 In our study, we found the average number of drugs prescribed was 5.56 per prescription. Similar studies carried out among geriatric patients in another place of Nepal, 17 Turkey, 18 USA, 13 India, 6 Brazil, 19 The less number of drugs prescribed in our study compared to studies conducted in other countries might be due to a functional health insurance policy for the elderly in those countries which might have provided easier access to medications. The most common form of morbidities found in this study was from cardiovascular system (47.0%) with hypertension.…”
Section: Discussionsupporting
confidence: 49%
“…Há ferramentas de orientação em alguns países, entretanto é necessário o desenvolvimento de listas nacionais, construídas com base em fármacos comercializados em cada país 20 .…”
Section: Discussionunclassified
“…In this study, it was observed that a higher prevalence occurred in the consumption of five or more medication drugs among the diabetic people. Here, it is important to reflect about the conditions under which polypharmacy occurs, considering that several studies have related this phenomenon to the inappropriate use of medication among elderly people 38,39 , which can be an aggravating factor to the adequate DM control in this population.…”
Section: Discussionmentioning
confidence: 99%